Analisis ‘Uruf dalam Teori Akuntansi Syari’ah - Erliyanti, Erliyanti; Yurmaini, Yurmaini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Financial institutions, such as banks, and financial products that adhere to the Islamic sharia system are growing, as is the idea of sharia accounting. The phenomenon of the emergence of two streams of formulation of sharia accounting theory in the form of idealistic and pragmatic streams raises problems and difficulties in the development of sharia accounting thought. The research approach and analysis of ideas used are both qualitative. The results of this study indicate that sharia accounting theory is an accounting theory that is intended to account for human actions in the field of asset management entrusted to them by those who give responsibility in an appropriate manner and comply with the sharia of Allah SWT. The aspect of faith requires that sharia accounting contain monotheism toward Allah SWT. The legal aspect of amaliyah makes sharia accounting based on the understanding that accounting behavior has the value of rights and obligations, sanctions, and rewards, which are interpreted from